Numerical research on biomass wastewater treatment using double-partition vessel with off-centered impellers - Zhang, Wei; Yang, Yijie; Qian, Wenmin; Ma, Longlong; Chen, Lungang; Liu, Na; Liu, Ying; Chen, Yubao (International Journal of Agricultural and Biological Engineering, 2023)
Limited by single function, it is difficult for the traditional stirred vessels to meet the requirements of mixing system in biomass wastewater treatment processes. The estimation of biomass wastewater stirring reactor performance by computational fluid dynamics (CFD) during multiphase reactions is important, due to the uncertainty in the numerical results. In this study, a novel double-partition stirred vessel with eccentrically located impellers was developed for the special subject. In addition, many simulations were carried out with the wastewater from biomass ethanol production as the medium to ensure the high reactor performance. The fluid flow was simulated and analyzed using the turbulent RNG k-ε model and multi reference frames. A good agreement is found between the simulation results and the confirmatory experiment. Moreover, the weir crest and interconnected pore were specially designed for the establishment of the circulation of fluid to maintain different technological conditions in the two regions. The distributions of radial velocities and tangential velocities were concentrated near the stirring blade. From the velocity profile, it is deduced that the flow pattern in the stirred vessel is insensitive to Reynolds number. Finally, this simulation study could contribute to the improvement and optimization of the structure, as well as the operation of the novel stirred vessel. Keywords: biomass, wastewater treatment, double-partition vessel, computational fluid dynamics DOI: 10.25165/j.ijabe.20231602.7637 Citation: Zhang W, Yang Y J, Qian W M, Ma L L, Chen L G, Liu N, et al. Numerical research on biomass wastewater treatment using double-partition vessel with off-centered impellers. Int J Agric & Biol Eng, 2023; 16(2): 232-240.